PENERAPAN PSAK NO. 45 PADA GEREJA GMIM BUKIT ZAITUN WALIAN DUA - Kumambow, Leonardo; Tinangon, Jantje J.; Tirayoh, Victorina Z. (Universitas Sam Ratulangi, 2015)
Disclosure of financial statements of the Church so important that financial accountability becomes clear, and can increase the confidence of donors and people who have given charity to the Church to manage the fund. Demands for accountability are adequate, especially for non-profit organizations of the Church can be overcome by applying general standards that apply in Indonesia, PSAK No. 45 on financial reporting nonprofits. The purpose of this study was to determine how the Financial Statements GMIM Olivet Church Walian Two when applying PSAK No. 45. The method used is descriptive qualitative method. The results obtained GMIM Olivet Church Walian Two prepare financial statements based on Tata's Church, where the financial statements prepared in the form of a report containing the budget realization of revenue and expenditure of the Church during the year. GMIM Olivet Church should apply PSAK No. 45 so that the financial statements would be more relevant, reliable, and can be compared to the accountability of the financial statements is adequate.